New tambos, old routes: the archaeology of mobility in the highlands of Tacna (AD 1830-1930) - Noa Corcoran-Tadd (Bulletin de l'Institut Français d'Études Andines)
Tacna and Arica played important roles through the colonial and post-colonial periods as points of connection between the Bolivian altiplano and a wider globalizing Pacific. Yet the rural landscapes of mobility and mining that shaped the strategic importance of the region remain poorly documented in the archival record. Drawing on archaeological research conducted on both sides of the Peru-Chile border, this paper explores the material evidence of commerce, mining, and consumption at a series of 19th-century rural tambos (waystations) in the highlands of Tacna and offers a new perspective on the region’s history as it was reshaped by liberalization, state building, and rural communities.